Dual-cut graphene transistors with constant-current regions fabricated by the atomic force microscope anode oxidation. (1st December 2016) - Wu, Chong-Rong; Dou, Kun Peng; Wang, Cheng-Hung; Chang, Chung-En; Kaun, Chao-Cheng; Wu, Chao-Hsin; Lin, Shih-Yen
Abstract: Graphene bandgap opening is an important issue for the application of this material. We have demonstrated that by atomic force microscope (AFM) anode oxidation, long nonconductive oxidation lines can be fabricated on graphene surfaces. By using this fabrication technique with the dual-cut transistor architecture, the phenomenon of constant-current regions near the Dirac point can be observed in devices at room temperature when the cut separation is smaller than 100 nm. The results may provide evidence of the phenomenon of graphene bandgap opening at room temperature. The theoretical bandgap values are further estimated by density-function-derived tight-binding calculations.